Traces: The Realities Surrounding the Missing and Murdered Indigenous Women Crisis, 2019 (2019)
An annual publication that is reported, photographed, edited, and designed by students in the University of Montana’s School of Journalism.https://scholarworks.umt.edu/nativenews/1027/thumbnail.jp